Thrift : the history of an American cultural movement - Yarrow, Andrew L. (University of Massachusetts Press, 2014)
"In this lively and engaging book, Andrew L. Yarrow tells the story of a national movement that promoted an amalgam of values and practices ranging from self-control, money management, and efficiency to conservation, generosity, and planning for the future -- all under the rubric of 'thrift'. Emerging in tandem and in tension with the first flowerings of consumer society, the thrift movement flourished during the 1910s and 1920s and then lingered on the outskirts of American culture from the Depression to the prosperous mid-twentieth century. A post-World War II culture that centered on spending and pleasure made the early-twentieth-century thrift messages seem outdated. Nonetheless, echoes of thrift can be found in currently popular ideas of 'sustainability', and 'simplicity' and in efforts to curtail public and private debt."--Back cover.